A new silver coin of the Gothic kingdom in Italy - Faltin, Dirk (KOINON: The International Journal of Classical Numismatic Studies, 2024)
This article discusses an extremely rare and historically significant series of coins minted during the last years of the Gothic kingdom in Italy. The coins, known as quarter-siliquae, were struck during the reign of king Totila/Baduila (541–552). Unlike the rest of the Gothic silver coinage, these coins show variants of the legend “INVICTISSIMVS AVTOR” (sc. AVCTOR), which can be translated as “the most invincible founder”. Totila/Baduila’s Invictissimus quarter-siliquae are exceptionally rare. Demo (2009) knew of only four specimens in three different variants. The aim of this article is to present a fifth specimen to the literature, which constitutes a new fourth variant, and to discuss the series in its historical and numismatic context.